2009
DOI: 10.4208/cicp.2009.v6.p131
|View full text |Cite
|
Sign up to set email alerts
|

Laplace-Transform Finite Element Solution of Nonlocal and Localized Stochastic Moment Equations of Transport

Abstract: Abstract. Morales-Casique et al. (Adv. Water Res., 29 (2006), pp. 1238-1255) developed exact first and second nonlocal moment equations for advective-dispersive transport in finite, randomly heterogeneous geologic media. The velocity and concentration in these equations are generally nonstationary due to trends in heterogeneity, conditioning on site data and the influence of forcing terms. Morales-Casique et al. (Adv. Water Res., 29 (2006), pp. 1399-1418) solved the Laplace transformed versions of these equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…To return into the real age‐domain, the fields gˆ(x,t,s) or trueρˆα(x,t,s) need to be numerically inverted. Various authors [e.g., see Sudicky , 1989; Cornaton , 2003; Cornaton and Perrochet , 2006a; Morales‐Casique and Neuman , 2009] have shown that the numerical inversion of Laplace transform finite element solutions are generally accurate when using the algorithm of Crump [1976] and when further combining it to the quotient‐difference algorithm, as proposed by de Hoog et al [1982]. The Laplace transform schemes can suffer from oscillations near discontinuities during the inversion, in relation to the nonuniform convergence of the series in the inversion formula.…”
Section: Numerical Solutions Of the Transient Age Distribution Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…To return into the real age‐domain, the fields gˆ(x,t,s) or trueρˆα(x,t,s) need to be numerically inverted. Various authors [e.g., see Sudicky , 1989; Cornaton , 2003; Cornaton and Perrochet , 2006a; Morales‐Casique and Neuman , 2009] have shown that the numerical inversion of Laplace transform finite element solutions are generally accurate when using the algorithm of Crump [1976] and when further combining it to the quotient‐difference algorithm, as proposed by de Hoog et al [1982]. The Laplace transform schemes can suffer from oscillations near discontinuities during the inversion, in relation to the nonuniform convergence of the series in the inversion formula.…”
Section: Numerical Solutions Of the Transient Age Distribution Equationmentioning
confidence: 99%
“…A control of these oscillations can be done by increasing the number of discrete Laplace variables NL=2n+1 and decreasing the mesh/grid size near discontinuities. It can be reported that a value for n ranging between 10 and 20 generally yields accurate solutions in the presence of sharp gradients [ Cornaton , 2003; Cornaton and Perrochet , 2006a; Morales‐Casique and Neuman , 2009].…”
Section: Numerical Solutions Of the Transient Age Distribution Equationmentioning
confidence: 99%
“…The time independency of the transformed diffusion problem (Equation ) renders its numerical solution possible without time stepping, and therefore avoids both the necessity to satisfy the stability condition which dictates smaller time steps for finer mesh and the requirement to compute the solutions for each time step regardless of the interest at a single time (e.g., Cai & Costache, 1994; Morales‐Casique & Neuman, 2009; Sudicky & McLaren, 1992).…”
Section: Derivation Of Hi‐fem For Diffusionmentioning
confidence: 99%
“…Numerical methods can similarly benefit from the Laplace transform, converting the time-dependence of a differential equation to parameter dependence. Laplace-space finite-element approaches have seen application to groundwater flow and solute transport (e.g., [Sudicky and McLaren(1992), Morales-Casique and Neuman(2009)]), and Laplace-space BEM has also been used in groundwater applications (e.g., [Kythe(1995), §10.3] or [Liggett and Liu(1982), §10.1]). The Laplace transform analytic element method [Kuhlman and Neuman(2009)] is a transient extension of the analytic element method.…”
mentioning
confidence: 99%